Evaluation of the Performance of the Investment and Integrated One-Stop Service Department (DPMPTSP) of Sidenreng Rappang Regency Through Public Satisfaction Survey - Ammar, Muhammad Ammar; Nurfajri Ardianti (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This research aims to evaluated the performance of the Investment and One-Stop Integrated Services department (DPMPTSP) of Sidenreng Rappang Regency through a community satisfaction survey. The method used in this research is employing a descriptive analysis approach, inferential analysis such as correlation analysis and quadrant analysis, and adding qualitative analysis using Word Cloud. In addition, the indicators used and the measurement procedures refer to the guidelines of Permenpan RB No. 14 of 2017. The data collection technique began with accidental sampling, selecting samples from individuals who are randomly encountered at the location and have just been served by the DPMPTSP, followed by filling out a questionnaire through face-to-face interviews. Based on the research results, the Public Satisfaction Index (IKM) of DPMPTSP obtained a score of 3.101, which falls into the "Good" category or a "B" score with a conversion value of 77.536. Based on the correlation analysis, a significant correlation was found between officer behavior and service procedures with a value of 0.464, categorized as "moderate correlation". Meanwhile, based on the quadrant analysis, the service elements located in quadrant II that need to be maintained are the cost/tariff and infrastructure. Based on the qualitative analysis of the Word Cloud, the community assesses the competence of the officers by their ability to serve quickly, skillfully use computers, and provide good service, while the community evaluates the officers' behavior based on their friendliness, politeness, and warmth in conversation